An extension of the Cheney-Sharma operator of the first kind - Cătinaș, Teodora; Buda, Iulia (J. Numer. Anal. Approx. Theory, 2023)
We extend the Cheney-Sharma operators of the first kind using Stancu type technique and we study some approximation properties of the new operator. We calculate the moments, we study local approximation with respect to a K-functional and the preservation of the Lipschitz constant and order.